Comparative Evaluation of the Environmental Culture of 8th Grade Students in Bulgaria and Turkey - Z. Kostova; E. Atasoy (University of Sofia, 2008)
The article reports the results from an investigation of the ecological and general scientific knowledge of students in the upper grade of elementary school (8th grade, 15 year old) in Bulgaria and Turkey with the aid of a questionnaire, containing 40 terms from ecology, geography, biology, chemistry, nature conservation, health and nutrition. It has allowed us to investigate the effects of several factors such as the students` social status (Turkey), the science education in school, school entrance exams in biology (Bulgaria), the interrelation between environmental and scientific knowledge, evaluation and self-evaluation, analysis and self-analysis. On the basis of the results and the conclusions of their analysis the students` achievements in respect to the state educational standards have been evaluated. Furthermore, adequate measures are recommended to teachers in order to overcome the deficiencies and shortcomings in students` knowledge and understanding. The research identifies several problems for future investigation